MODELS OF NEEDS DEFINING IN SOCIAL SERVICES IN THE CONTEXT OF SOCIO-CULTURAL CHANGES - Люта, Леся Петрівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article deals with the analysis of the needs of social work customers. It is revealed, that the constant change of social situation signiﬁ cantly inﬂ uences the character and the content of the population social demand. Rapid dynamics of social and cultural changes, which is observed in Ukraine, complicates the solution of social problems. The effective ways of ﬁ nding out the customers’ needs, which are used in different countries of the world, are presented. The model of differences, taking decisions and the marketing model are analyzed. The system of measures, which are aimed at the monitoring and evaluation of needs in social services is studied, the speciﬁ c character of the work with the customers in the state and civil organizations is deﬁ ned. It is found out, that the monitoring of needs depends on the category of the customers and the possibilities for the employees of social sphere to cover the territory. The criteria of deﬁ ning actual needs are deﬁ ned. The mechanism of collective efforts of the state, non-state, civil and business sectors for the organization of social work is suggested.